46‐2: Invited Paper: A Flexible OLED Display with Robustness and Bendability. Issue 1 (29th May 2019) - Eguchi, Shingo; Kato, Sho; Kamada, Taisuke; Suematsu, Yui; Nakamura, Daiki; Nagata, Takaaki; Aoyama, Tomoya; Sugisawa, Nozomu; Toyotaka, Kouhei; Katayama, Masahiro; Adachi, Hiroki; Yamazaki, Shunpei
Abstract : This study aims to focus on a cover film with a considerably low Young's modulus to achieve robust and flexible displays. We fabricated a prototype flexible display with such a film on its surface and achieved a display with robustness and bendability, which can be used in various applications.